KEKERASAN DALAM RUMAH TANGGA PADA IBU HAMIL DI MASA PANDEMI COVID-19 - Fajarini, Nurbita; Wardani, Suci Fitriana Pramudya (STIKES Borneo Cendekia Medika, 2024)
A shadow pandemic in the form of violence against women, especially domestic violence, is one of the impacts of the COVID-19 pandemic. Unfortunately, there has not been much research on domestic violence specifically for pregnant women during the COVID-19 pandemic. This literature review aims to summarize research evidence on domestic violence in pregnant women during the COVID-19 pandemic. Articles were obtained from three databases (PubMed, ScienceDirect, and ProQuest) with an English filter and published in 2019–2022. After a series of selection processes, seven articles that met the criteria were obtained, giving a total sample of 8725. There were 4 main themes found in this literature review, namely the prevalence of domestic violence, types of domestic violence, factors influencing the occurrence of domestic violence, and the impact of domestic violence on pregnant women. The high prevalence and severe impact of domestic violence on pregnant women during the COVID-19 pandemic must be a common concern as a problem in public health. Related parties, especially health service providers, must play an active role in preventing and dealing with domestic violence in pregnant women.